Damage mechanism of composite laminates under multiple ice impacts at high velocity - Zhu, Xinying; Fu, Xinqiang; Liu, Lulu; Xu, Kailong; Luo, Gang; Zhao, Zhenhua; Chen, Wei (International journal of impact engineering, 2022)
•Different impact schemes including single-point and multi-point impact were carried out.•Three routes including visual analysis, C-Scan analysis and X-ray tomography were used to observe the intralaminar and interlaminar damage patterns.•An innovative damage category induced by multiple ice impacts were summarized.•The sequence and morphology of delamination damage between plies are different in single-point and multi-point impact.•A strain-rate dependent continuum damage model with interlayer cohesive element was successfully used to evaluate the damage behavior in CFRP laminates. Unlike most research on ice impact threats with single impact and multiple repeated impact, different impact schemes such as single-point repeated impact and multi-point sequential impact were carried out in this article, considering the actual circumstance of hail impacts on aerospace structures. To study the response of CFRP laminates to multiple ice impacts, ice projectiles with a diameter of 25 mm were projected onto laminates. Three different routes, including visual analysis, C-Scan analysis and X-ray tomography, were then used to observe the intralaminar and interlaminar damage patterns. An innovative damage category induced by different impact schemes was summarized from the whole experimental results through the visual analysis. The extent of delamination damage was characterized by C-Scan and CT. Both the damage mode and the area of delamination are not only related to the magnitude of single impact energy, but also to the density of impact points. For numerical approach, a strain-rate dependent continuum damage model with interlayer cohesive element was used to predict the damage evolution in CFRP laminates. It was first verified and then combined with the test data to reveal different damage mechanisms of single-point repeated impact and multi-point sequential impact.